2022
DOI: 10.3390/agriculture12030391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dorper Rams’ Social-Sexual Hierarchy on Their Sexual Behavior and Capacity to Induce Estrus in Ewes

Abstract: This study aimed to assess the influence of the social rank of rams and quality of stimuli to ewes between dominant and subordinate Dorper rams joined to anestrus ewes. Social rank was evaluated for two days (ESR; n = 36); rams were exposed to estrogenized ewes in a competitive test. According to the reproductive response, anovulatory ewes (n = 76) were divided into two groups: LHRe (n = 38; ewes exposed to four low hierarchy rams (LHR)) and HHRe (n = 38; ewes exposed to four high hierarchy rams (HHR)). Regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(48 reference statements)
0
5
0
1
Order By: Relevance
“…High-social-ranked males displayed a greater number of threatening behaviors associated with greater sexual appetitive and consummatory actions [ 11 ]. As previously reported in Corriedale x Milchschaf rams, an increase in sexual appetitive and consummatory behaviors may be linked to the fact that threatening behaviors raise the voluntary feed intake [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-social-ranked males displayed a greater number of threatening behaviors associated with greater sexual appetitive and consummatory actions [ 11 ]. As previously reported in Corriedale x Milchschaf rams, an increase in sexual appetitive and consummatory behaviors may be linked to the fact that threatening behaviors raise the voluntary feed intake [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hierarchy, high-social-rank (HSR) rams show a greater number of appetitive and consummatory sexual behaviors than low-social-rank (LSR) rams; however, said sexual behavior is highly correlated to the live weight of males [ 11 ]. Moreover, the importance of live weight for reproductive success is greater for males than for females [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding self-breeding in an open environment, it has been shown that no relationship exists between dominance and mating behavior (Ungerfeld et al, 2019). Although it rarely happens, in the mating process with only one ram, there is a possibility that there is a dominating ewe, especially those with a larger and more aggressive body, which causes rivalry among ewes for a ram and can result in a lower pregnancy rate (González-Tavizón et al 2022). Nevertheless, with the high active behavior of ewes in outdoor pen treatment and the continuous presence of a ram, there is a significant level of social interaction between ewes and rams.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that the males of the CG presented a greater appetitive sexual behavior. Indeed, rams exposed to anovulatory ewes exhibit intense sexual behavior (nudging, pawing, anogenital sniffing) (Calderón-Leyva et al 2018;González-Tavizón et al 2022). During the male effect, goats placed in contact with seasonal anestric goats show intense appetitive sexual behavior (e. g., nudging, anogenital sniffing, vocalizations) (Ponce et al 2014;Hernández-Ruiz et al 2021).…”
Section: Sexual Behavior Of Ramsmentioning
confidence: 99%